(untitled) (Bangladesh Journal of Botany, 2023)
Development of the effective canopy architecture management for optimum light interception, and planting density on significant yield and fruit quality of Litchi cv. Shahi was investigated. The litchi cv. Shahi, planted in square system at 2 × 2, 3 × 3, 4 × 4, 5 × 5, 6 × 6 and 8 × 8 m (control), showed average light interception higher in the upper part of the canopy. Flowering and yield attributes (number of panicles, panicle length, number of flowers and fruit yield/plant) were obtained maximum in wider spaced trees (8x8 m) while fruit yield kg/plant was recorded maximum in 6x6 m in square system of planting. Fruits harvested from 8x8 m trees were superior in fruit quality (fruit length, weight, diameter, total soluble solids, organoleptic score, TSS: Acidity). Biochemical parameters and leaf nutrient content (total phenol, N, P, K and total chlorophyll, total sugar) were recorded maximum in 8x8 m. Hence, 8x8 m planting space can be recommended to the farmers for better yield. Bangladesh J. Bot. 52(1): 165-170, 2023 (March)